ZPT Growtone dan Pemberian Pupuk NPK 16-16-16 Meningkatkan Pertumbuhan Stek Pucuk Tanaman Jambu Air Madu ( Syzygium aquaeum ) - Didik Darmaji; Nurma Ani; Aisyah Lubis (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Al Azhar Medan, 2023)
This research was carried out on Jl. Makmur, Dusun III Banyumas Village, Stabat District, Langkat Regency, North Sumatra This research was carried out from December to March 2022. Materials used: Water-honey guava brood tree, honey-water guava shoots of green delli variety, Growtone, Npk 16-16-16 Fertilizer. This study was arranged based on a factorial randomized block design (RAK) with 2 treatment factors and 3 replications. The first factor was the administration of Growtone consisting of 4 levels, namely: G0: Without Growtone (control), G1: 0.5% (5 gr100 ml-1). water), G2: 1.0% (10 gr100 ml water-1), G3: 1.5% (15 gr100 ml water-1). The second factor is the application of NPK 16-16-16(N) fertilizer consisting of 3 The levels are: N0: Without NPK 16-16-16 fertilizer (control), N1: 0.2 g100 ml water-1, N2: 0.4 g 100 ml water-1. The results of the study showed that the application of ZPT Growtone had a very significant effect on the parameters of the longest root length and the number of roots, had a significant effect on the parameters of plant height, number of leaves, and number of shoots, but had no significant effect on the parameters of the percentage of cuttings growing. The application of NPK 16-16-16 fertilizer had a very significant effect on the parameters of plant height, significantly on the parameters of the number of leaves, the number of shoots, the longest root length, and the number of roots, but had no significant effect on the parameters of the percentage of cuttings growing. The interaction of giving zpt growtone and giving NPK 16-16-16 fertilizer had no significant effect on all observation parameters